The Impact of Remote Visualized Teaching on Clinical Competence Following Short-Term Bronchoscopy Training - Wang S; Song D; Sun X; Li C; Wang H; Ma J; Li W (Advances in Medical Education and Practice)
Shupeng Wang,1 Dejing Song,1 Xiaocong Sun,1 Chen Li,1 Hui Wang,1 Junyu Ma,1 Wei Li2 1Intensive Care Unit, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 2Health Check-up Center, China-Japan Friendship Hospital, Beijing, People’s Republic of ChinaCorrespondence: Wei Li, Health Check-up Center, China-Japan Friendship Hospital, Beijing, People’s Republic of China, Tel +86 15652749107, Email web_document@163.comObjective: To evaluate the impact of remote visualized teaching (RVT) on trainees’ confidence and clinical competence after short-term traditional simulation-based bronchoscopy training.Methods: In this prospective self-controlled quasi-experimental study, two cohorts, with 24 trainees each, completed a one-day traditional bronchoscopy course and voluntarily joined a one-month RVT program. Confidence and clinical competence were evaluated before and after RVT using the Bronchoscopy Operator Confidence Scale (BOCS) and a modified Ontario Bronchoscopy Assessment Tool (OBAT), with scores analyzed using the Wilcoxon signed-rank test.Results: 48 trainees from 43 hospitals (81.2% secondary-level) completed the RVT course. Median BOCS scores increased significantly from 60.0 (54.0– 64.0) to 75.0 (72.0– 81.0; p< 0.001), with notable improvements in emergency response (2.00→ 3.50) and operational skills (2.75→ 3.50). Modified OBAT scores rose from 66.7 (60.7– 74.4) to 79.7 (76.7– 84.9; p< 0.001), notably, there were significant improvements in the scores for operational skills, diagnostic abilities, and post-procedure management.Conclusion: Remote visualized teaching significantly enhances trainees’ confidence and clinical competence, serving as a valuable adjunct to traditional bronchoscopy education.Keywords: bronchoscopy, training, remote visualized teaching, clinical competence